Protéger un paysage culturel évolutif vivant. Enjeux et contraintes dans le bassin minier du Nord-Pas-de-Calais, patrimoine mondial de l’Unesco - Camille Mortelette (Bulletin de l’Association de Géographes Français, 2024)
The combined work of man and nature, cultural landscapes express the long and intimate relationship between peoples and their environment" (UNESCO definition). Even if they are described as continuing, they should be preserved so that they reflect the relationship between people and the environment. Nevertheless, this relationship is regularly considered to be under threat. In the case of the Nord-Pas-de-Calais Mining Basin, it is particularly recent urban forms that are considered to be a source of trouble by planning professionals. This paper looks at the normative visions and tools of the Mission Bassin Minier, in charge of the management plan for the Unesco listing, and the paradoxes of trying to maintain the universal and exceptional value of a cultural landscape that is said to be continuing.